2014
DOI: 10.1111/ped.12233
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prediction of outcome in hypoxic–ischemic encephalopathy in Japan

Abstract: BackgroundHypoxic–ischemic encephalopathy (HIE) is one of the most critical pathologic conditions in neonatal medicine due to the potential for neurological deficits in later life. We investigated the incidence of term infants with moderate or severe HIE in Japan and identified prognostic risk factors for poor outcome in HIE.MethodsData on 227 infants diagnosed with moderate or severe HIE and born between January and December 2008 were collected via nationwide surveys from 263 responding hospitals. Using logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 33 publications
0
33
2
2
Order By: Relevance
“…We would expect to see 1,000–2,000 cases of neonatal encephalopathy each year given that the incidence of neonatal encephalopathy is approximately 1–2 per 1,000 live births in developed countries21, but just over 500 cases were recorded in the registry over 3 years. Hayakawa and colleagues have, however, estimated that the incidence of moderate to severe neonatal encephalopathy in Japan is 0.37 per 1,000 live births22. Considering that 219 of 287 registered level II-III neonatal intensive care centres participated in the current registry (76.3%), our database is likely to have included the majority of eligible neonates.…”
Section: Discussionmentioning
confidence: 99%
“…We would expect to see 1,000–2,000 cases of neonatal encephalopathy each year given that the incidence of neonatal encephalopathy is approximately 1–2 per 1,000 live births in developed countries21, but just over 500 cases were recorded in the registry over 3 years. Hayakawa and colleagues have, however, estimated that the incidence of moderate to severe neonatal encephalopathy in Japan is 0.37 per 1,000 live births22. Considering that 219 of 287 registered level II-III neonatal intensive care centres participated in the current registry (76.3%), our database is likely to have included the majority of eligible neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical, laboratory, electrophysiological, and imaging measures have been used to predict the coincident and subsequent potential brain damage with the aim of developing decisive prognostic criteria 8. Scoring systems to help predict death and disability have been subjected to continual stringent assessment and validation 9. However, this has not been the case for acute-stage parameters predictive of occurrence and short-term outcomes 10…”
Section: Introductionmentioning
confidence: 99%
“…(9) During our study, no patients developed polycythemia and venous thromboses.Unlike previous study, we focused on several potential neurological outcome related biomarkers which were widely detected in routine clinical work. Evidence revealed high serum level of CK and LDH was contributed to poor outcome in HIE neonates (14,26). Our results showed higher level of CK decreased obviously in both group after treatment, while average level of CK in Epo group was closer to normal value than placebo group.…”
mentioning
confidence: 43%
“…CK, usually used in judging myocardial ischemic injury, have also been found that high level was associated with serious brain damage. (14) LDH, one of the important enzyme participating in anaerobic glycolysis and gluconeogenesis, have been demonstrated the level was signi cantly higher in the HIE group. (15) Besides, HI triggers the disruption of ionic homeostasis, characterizing by enhanced K + e ux and Na + , Ca 2+ in ux, which has been considered as the most important alteration which eventually leads to cell death or injury.…”
Section: Potential Neurological Biomarkersmentioning
confidence: 93%